Analysis of disease trends in children and adolescents with mental disorders of a general hospital in Chengdu during public health emergencies - Shi Lixin; Qiu Changjian (Sichuan jingshen weisheng)
BackgroundChildhood and adolescence are critical stages in psychological development. During the public health emergencies， children and adolescents exhibit weaker psychological coping ability， making them more vulnerable to mental health issues.ObjectiveTo investigate trends in the distribution of hospitalized children and adolescents patients at mental health centers of a general hospital during public health emergencies， so as to provide references for future research and intervention for adolescent under similar contexts.MethodsA retrospective cohort study was conducted on 6 613 children and adolescent patients hospitalized and discharged from the Mental Health Center of West China Hospital， Sichuan University， from January 1， 2018 to December 31， 2022. Patients were included if their primary diagnosis was schizophrenia， schizotypal disorder and delusional disorder， depressive disorder， bipolar disorder， anxiety disorder or post-traumatic stress disorder in International Classification of Diseases， tenth edition （ICD-10）. Patients were divided into two groups based on their admission period： pre-COVID-19 pandemic period （from January 1， 2018 to December 31， 2019） and during the COVID-19 pandemic （from January 1， 2020 to December 31， 2022）. Trends in diagnostic distributions were analyzed using the trend chi-square test.ResultsSignificant differences were observed between pre-pandemic and pandemic periods in age， length of hospital stay and sex（t=10.743， 4.082， χ2=29.092， P<0.01）. During the COVID-19 pandemic， the proportions of depressive disorder， bipolar disorder and anxiety disorder among hospitalized children and adolescents patients increased （χ2trend=11.058， 67.333， 17.276， P<0.01）， while the proportions of schizophrenia， schizotypal disorder and delusional disorder decreased （χ2trend=219.924， P<0.01）. Among patients aged 6~14 years， the proportion of bipolar disorder increased （χ2trend=18.207， P<0.01）. Among patients aged 15~19 years， the proportion of bipolar disorder and anxiety disorder also increased （χ2trend=57.339， 19.011， P<0.01）. In male patients， the proportions of depressive disorder and bipolar disorder increased （χ2trend=21.729， 11.380， P<0.01）， while in female patients， the proportion of bipolar disorder and anxiety disorder increased （χ2trend=54.830， 14.377， P<0.01）.ConclusionCompared with the pre-pandemic period， during the COVID-19 pandemic， among hospitalized children and adolescents patients， there are more female patients than male patients， with a tendency for patients to be younger and have shorter lengths of hospital stay. The proportions of depressive disorder， bipolar disorder and anxiety disorder have all increased.